PEDESIGNING BUSINESS STRATEGY FOR UNGGAS DISTRIBUTOR IN MARKET EXPANSION EFFORTS - Natanael Tedjakusuma; Denpharanto Agung Krisprimandoyo (International Journal of Economic Integration and Regional Competitiveness, 2024)
General Background: The poultry industry plays a vital role in meeting the demand for essential food ingredients, particularly chicken meat, which is a staple protein source. Specific Background: However, a decline in sales revenue and market instability faced by poultry supplier companies necessitates strategic solutions to address these challenges. Knowledge Gap: Despite the availability of business strategies, limited research focuses on targeted approaches for optimizing market expansion in poultry distribution. Aims: This study aims to design a business strategy for a poultry supplier company to enhance its sales performance, specifically in chicken meat distribution, through the application of the Quantitative Strategic Planning Matrix (QSPM) method. Methods: Utilizing a qualitative phenomenological approach, this research was conducted from February to June 2024, involving four informants. Data were collected through interviews and observations, with source triangulation employed to ensure validity. Results: The SWOT analysis revealed that the company is positioned in Quadrant II, signifying the need to address weaknesses to leverage opportunities. Strategies identified include market penetration and market development to secure and expand into new markets. The study prioritizes market penetration through the expansion of chicken meat distribution across Surabaya, supported by technology-driven promotional efforts such as product marketing and content creation. Novelty: This research offers a tailored approach by integrating strategic planning with technological applications to address market-specific challenges. Implications: The findings provide actionable insights for poultry suppliers, highlighting the importance of technological utilization and strategic market expansion to achieve sustainable growth and improve competitiveness in the food supply industry.